The Influence of Self-Efficacy, Locus of Control, and Financial Literacy on the Digital Financial Behavior of Accounting Students at Muhammadiyah University Makassar - Vivin Vivin; Amril Amril; Zalkha Soraya (Economos : Jurnal Ekonomi dan Bisnis, 2026)
This study aims to determine the effect of self-efficacy, locus of control, and financial literacy on the digital financial behavior of accounting students at Muhammadiyah University of Makassar. This study used a quantitative approach with a sample of 100 respondents and data analysis using multiple linear regression with the help of SPSS version 27, and supported by validity, reliability, and hypothesis testing. The results showed that self-efficacy partially had a positive and significant effect on digital financial behavior with a t-value of 3.046 > 1.984 and a significance value of 0.003 < 0.05. Locus of control has a positive and significant effect on digital financial behavior, with a t-value of 2.605 > 1.984 and a significance value of 0.011 < 0.05. Meanwhile, financial literacy has a positive but insignificant effect on digital financial behavior, with a t-value of 0.802 < 1.984 and a significance value of 0.425 > 0.05. Simultaneously, self-efficacy, locus of control, and financial literacy significantly influence digital financial behavior, with an F-value of 18.764 and a significance value of 0.000 < 0.05.